Staphylococcus haemolyticus Profiles that Carrier of IE Gene as Nosocomial Infection in a Hospital Environment - Obeid, Ali J.; Naser, Maryam S. (Scientific Journal of Medical Research, 2023)
In the presented study, 40 clinical Staphylococcus haemolyticus isolates were isolated from 200 patients admitted to Marjan Teaching Hospital in Babylon Governorate. Those (40) isolates were isolated from 15 males and 25 females from blood, urine and skin. The isolates were diagnosed as S. haemolyticus using the biochemical test, API Staph System, Vitek2 compact system and culture assays, and identified by polymerase chain reaction PCR. The biofilm-forming capacity was examined by the microtiter plate method. S. haemolyticusn showed That the total number of isolates that formed biofilm is 33 distributed among 28 (70%) isolates that formed strong biofilm and 5 (12.5%) moderate, while 7 (17.5%) don’t form biofilm. The virulence atlE gene was detected by polymerase chain reaction. atlE gene. PCR analysis of the virulence agent atlE gene in S. haemolyticus isolates revealed that 10 (25%) of bacteria isolates were positive for this gene, indicating a link between biofilm and the atlE gene.